The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.17306/j.npt.2016.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glycolysis process in bulls’ meat carcasses subjected to different tenderization treatments

Abstract: SummaryBackground. Electrical stimulation and conditioning of carcasses are carried out to improve the quality of meat. The aim of the study was to evaluate the effect of these treatments on the glycolysis process and tenderness of beef. Material and methods. The longest lumbar muscles (m. longissimus lumborum) were the experimental material. They were divided into four groups by tenderization treatments: ES -high voltage electrical stimulation, KD -conditioning for 18 h at a temperature of 12-15°C, ES+KD -ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Especially, fat-associated genes have been screened in intramuscular fat, and the level of Gpam is significantly positively correlated with carcass grade in Hanwoo [10]. While lipid metabolic genes seem to be important, another feature of high grade carcasses is the induction of glycolysis after tenderization processes such as electrical stimulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, fat-associated genes have been screened in intramuscular fat, and the level of Gpam is significantly positively correlated with carcass grade in Hanwoo [10]. While lipid metabolic genes seem to be important, another feature of high grade carcasses is the induction of glycolysis after tenderization processes such as electrical stimulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…These changes are the direct cause of the ES meat tenderness improvement, and are the beginning of autolytic proteolysis and indirectly affect the changes in meat tenderness during ageing (Żywica, ). Iwańska et al () examined the influence of ES and ES in combination with conditioning (12–15 °C for 18 hr) and showed that ES improved meat tenderness, whereas the combination of ES and conditioning did not cause significant changes in the process of glycolysis and meat tenderization. White, O'Sullinan, Troy, and O'Neill (), who used ES in combination with the slow method of half‐carcasses chilling (10 °C for 10 hr and 2 °C for 48 hr) noted an increase in meat tenderness compared with the fast chilling method (2 °C for 48 hr).…”
Section: Introductionmentioning
confidence: 99%